Community Awareness on the Republic Act 11313 Known as the Safe Space Act of 2019 at Barangay 176 Bagong Silang, Caloocan City: An Assessment: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Republic Act 11313, also known as The Safe Space Act of 2019, is the stated Bill thatsought to protect both the public's safety and everyone’s sense of privacy. The law focuses ongender-based sexual harassment in public locations, such as streets, privately heldestablishments that are accessible to the public, and public transportation. The declared goalof the bill that created the Bawal Bastos Law was to safeguard both public safety and eachperson's right to privacy. Because men and LBGTQ people also commonly hear obscenityoutside, the ban on profanity rule was implemented as RA 11313 cases worsened. This lawwas enacted in order to shield people from those who have done nothing except cause troublefor others.Based on the results of the survey, it can be concluded that there is a significant issue ofgender-based sexual harassment in Barangay 176 Bagong Silang, Quezon City.Based on the recommendation, Increasing the penalties for the second offender of sexualharassment. Referral to another appropriate authority for review for possible violation of Stateand Federal statutes may also be appropriate. Referral for training, referral for counseling,Suspension, reassignment, demotion, or termination of employment, Written or verbalreprimand.
Keywords: Criminology